Financial Technology (fintech) a New Transaction in Future - Vieqi Rakhma Wulan (JEECS (Journal of Electrical Engineering and Computer Sciences), 2017)
The development of technology is so rapidly. The existance of technology is utilized for various business field.Telecommunication, book, film, transportation and now financial industry compete to take advantage of technology.Financial industry has long played in technology, often called with FinTech (Financial Technology). Credit cards,ATM, Bank mainframe computer are some of their products that utilize technology. The development of FinTech makea lot of start-Up glance at this field. In Indonesia, FinTech also quite developed. This research is focuse on how thepractise of FinTech in Indonesia. Where Indonesia still needs some preparation such as the mature of technology,resources, users and regulation.